Effect of Science Flipbook Based on Learning Styles and Multiple Intelligences (LSMI) For Facilitating Students’ Understanding and Critical Thinking Skills - Safitri, Fibriyana; Rusdiana, Dadi; Samsudin, Achmad; Widiyatmoko, Arif (Journal of Posthumanism, 2025)
The purpose of this research is to develop flipbook based on LSMI, analyze the increase in students' understanding and critical thinking skills, and analyze the effectiveness of flipbook. This research is a design-based research, where the development model used is the ADDIE model. The developed flipbook contain features arranged in such a way as to facilitate students with different learning styles and dominant intelligences, as well as train students' understanding and critical thinking skills. This flipbook has met the eligibility criteria in the aspects of content, language, presentation, and graphics. The increase in students' understanding is classified as moderate and the increase in students' critical thinking skills is classified as low. In addition, the effectiveness of flipbook in improving students' understanding and critical thinking skills are included in the large category.